The craft of university teaching - Lindsay, Peter, 1958- (University of Toronto Press, 2018)
"What does university teaching--as a craft--look like? What changes to a professor's educational philosophy does it require? What changes does a craft perspective suggest for higher education? The Craft of University Teaching addresses these questions in both a general sense, and with respect to the practical, everyday tasks of university professors, such as the use and misuse of technology, the handling of academic dishonesty, the assignment of course reading, and the instilling of enthusiasm for learning. Intended for professors of all academic disciplines who either enjoy teaching or wish to enjoy it more, The Craft of University Teaching is a provocative and accessible book containing practical advice gleaned from the academic literature on pedagogy. In an era of increased bureaucratic oversight, rapidly diminishing budgets, and waves of technological distraction, The Craft of University Teaching provokes reflection on matters of pedagogy that are too often taken as settled. In so doing, it seeks to reclaim teaching as the intellectually vibrant and intrinsically rewarding endeavor that it is."--